2010
DOI: 10.1029/2009jf001293
|View full text |Cite
|
Sign up to set email alerts
|

A spatially calibrated model of annual accumulation rate on the Greenland Ice Sheet (1958–2007)

Abstract: Past estimates of Greenland Ice Sheet accumulation rates have been multiyear climatologies based on ice/firn cores and coastal precipitation records. Existing annually resolved estimates have incompletely quantified uncertainty, owing primarily to incomplete spatial coverage. This study improves upon these shortcomings by calibrating annual (1958–2007) solid precipitation output from the Fifth Generation Mesoscale Model modified for polar climates (Polar MM5) using firn core and meteorological station data. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
193
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(221 citation statements)
references
References 52 publications
21
193
7
Order By: Relevance
“…A clear gradient in the thickness of each layer and in the associated estimates of annual accumulation is seen along the transect, with a 33.6% ± 16% mean decrease in accumulation from west to east each year. This trend has been observed in previous studies (Fischer et al, 1995;Anklin and Stauffer, 1994;Burgess et al, 2010) and reflects the dominant transport of water vapour in the region from west to east. Inter-annual variability in accumulation has also been observed previously (Fischer et al, 1995).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A clear gradient in the thickness of each layer and in the associated estimates of annual accumulation is seen along the transect, with a 33.6% ± 16% mean decrease in accumulation from west to east each year. This trend has been observed in previous studies (Fischer et al, 1995;Anklin and Stauffer, 1994;Burgess et al, 2010) and reflects the dominant transport of water vapour in the region from west to east. Inter-annual variability in accumulation has also been observed previously (Fischer et al, 1995).…”
Section: Discussionsupporting
confidence: 86%
“…Meanwhile, there are reports of an increase in the surface elevation at higher altitudes since 1990 (Krabill et al, 2000;Nghiem et al, 2005;Hanna et al, 2006), supporting calibrated climate models which show that some regions of the ice sheet have experienced higher than average accumulation rates, especially in the south (Burgess et al, 2010). A recent modelling study found larger than average accumulation rates across the GrIS between 1958 and 2007, and that the surface mass balance over the same period is between 32-63% higher than previous estimates (Ettema et al, 2009).…”
Section: Introductionmentioning
confidence: 58%
“…cs.umt.edu/isis/index.php/SeaRISE_Assessment), which is fairly similar to our inversion setup. The datasets include mean annual surface temperature from Fausto et al [2009], precipitation rates from Burgess et al [2010], basal heat flux from Shapiro and Ritzwoller [2004], and bedrock topography, ice thickness and surface elevation from Bamber et al [2001]. Observed surface velocities are also provided by Joughin et al [2010] and filled with balance velocities [see, e.g., Bamber et al, 2000] in the areas where observations are not available.…”
Section: Input Data and Model Setup 511 Input Datamentioning
confidence: 99%
“…Cores 6945 and 6943 (named for the coordinates where they were acquired) are ∼ 18 m long and extend back to 1976 while core 6941 is 11.7 m long and extends to a depth equating to 1985's accumulation. The thickness of the different annual layers is affected by annual snowfall, deflation and redeposition by wind, compaction, and melting, and varies on the order of tens of cm from year to year in western Greenland (McConnell et al, 2000;de la Peña et al, 2010;Burgess et al, 2010). Small amounts of ice are commonly found in the core, but are not present on an annual basis.…”
Section: Methods and Observationsmentioning
confidence: 99%